Prototype Robot Pengantar Barang Pengikut Marka Hitam Berbasis Mikrokontroller - Herman, Yurico; Hasibuan, Ade Zulkarnain; Sembirimg, Arnes (Forum Kerjasama Pendidikan Tinggi, 2024)
Robotics has become an ever-growing field with increasingly diverse applications in various industries. One interesting application is the development of delivery robots that can follow specific paths on surfaces using black markings as a guide. This research aims to design and implement a microcontroller-based black mark following goods delivery robot prototype. This robot prototype uses a TCRT5000 sensor to read black markings placed on the bottom of the robot. Using this robot is very easy by providing a battery for the robot's power source. The TCRT5000 sensor is a reading sensor for following the path. The FC-51 IR sensor as an obstacle detection sensor is in front of the robot for temporary stops when the robot is walking. The TTP223B touch sensor calibrates the robot at the start and end of the robot's work, inputting the additional number of stops when the robot is in a temporary state. This robot is easy to use because the operation is easy to understand, making the robot easy for ordinary people to use.